(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
In this work, we intend to propose some lines for literary cartography taken in a metaphorical sense Not only of the art of drawing maps but of investigating the perspectives and visions that the writing of many Argentine authors offers. Corpus was defined by the concern aroused by the influx and power of these voices in the last 20 years. With this, we do not intend to deny the previous existence of women in Argentine writing nor to make this a feminist study. Yes, on the other hand, affirm as Liliana Heker does that “man or woman, every artist has a peculiar and eccentric look, a distorting look that turns repulsive or geometric or parodic or beautiful a fact that lacked a previous sign. "This distortion of the norm is what allows the viewer-reader of an artistic fact to notice that norm and reformulate the world."